2021
DOI: 10.1039/d1cp03204f
|View full text |Cite
|
Sign up to set email alerts
|

Probing the influence of Zn and water on solvation and dynamics in ethaline and reline deep eutectic solvents by 1H nuclear magnetic resonance

Abstract: A range of ethaline and reline deep eutectic solvents (DESs) have been investigated in the absence and presence of Zn (0 - 0.3 M) and water (0 - 29 wt.%)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…It is revealed that the correlation between −NH 2 and −OH should be originated from the proton exchange behavior. This is different from the idea as proposed by AlZahrani et al Details of the motion and chemical exchange study will be discussed in the section of MD investigation in this article.…”
Section: Resultsmentioning
confidence: 72%
See 3 more Smart Citations
“…It is revealed that the correlation between −NH 2 and −OH should be originated from the proton exchange behavior. This is different from the idea as proposed by AlZahrani et al Details of the motion and chemical exchange study will be discussed in the section of MD investigation in this article.…”
Section: Resultsmentioning
confidence: 72%
“…According to 1 H spectrum, all the signals present a broad line shape. This is ascribed to the high viscosity of pure reline, which has been widely investigated in published works. ,, To further study the liquid structure of R-0, NOESY, COSY and ROESY experiments were conducted. As shown in Figure c, in NOESY spectrum, correlations between alkyl protons and −NH 2 protons were probed, especially for −CH 3 with more enhanced signal.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is interesting that although the local environment of H + was the same, T1 relaxation time was increased by addition of amines, suggesting that OH − was more strongly solvated and H + is more mobile and so mobility of Zn 2+ may also be increased by addition of amines. 30,31 This increased T1 relaxation time also suggests that the solvated structure of Zn(OH) 2 is more polarized, and the electron density on solvated Zn 2+ is delocalized by the strong electronic interaction between the added amine and solvated H 2 O, and so, the coordination…”
Section: ■ Results and Discussionmentioning
confidence: 97%